Transcriptomic Analysis of Trichoderma atroviride Overgrowing Plant-Wilting Verticillium dahliae Reveals the Role of a New M14 Metallocarboxypeptidase CPA1 in Biocontrol - Morán-Diez, María E.; Carrero-Carrón, Irene; Rubio, M. Belén; Jiménez-Díaz, Rafael M.; Monte, Enrique; Hermosa, Rosa (Frontiers in Microbiology, 2019)
Verticillium dahliae, a vascular-colonizing fungus, causes economically important wilt diseases in many crops, including olive trees. Trichoderma spp. have demonstrated an effective contribution as biocontrol agents against this pathogen through a variety of mechanisms that may involve direct mycoparasitism and antibiosis. However, molecular aspects underlaying Trichoderma–V. dahliae interactions are not well known yet due to the few studies in which this pathogen has been used as a target for Trichoderma. In the present study, Trichoderma atroviride T11 overgrew colonies of V. dahliae on agar plates and inhibited growth of highly virulent defoliating (D) V. dahliae V-138I through diffusible molecules and volatile organic compounds produced before contact. A Trichoderma microarray approach of T11 growing alone (CON), and before contact (NV) or overgrowing (OV) colonies of V-138I, helped to identify 143 genes that differed significantly in their expression level by more than twofold between OV and CON or NV. Functional annotation of these genes indicated a marked up-regulation of hydrolytic, catalytic and transporter activities, and secondary metabolic processes when T11 overgrew V-138I. This transcriptomic analysis identified peptidases as enzymatic activity overrepresented in the OV condition, and the cpa1 gene encoding a putative carboxypeptidase (ID number 301733) was selected to validate this study. The role of cpa1 in strain T11 on antagonism of V-138I was analyzed by a cpa1-overexpression approach. The increased levels of cpa1 expression and protease activity in the cpa1-overexpressed transformants compared to those in wild-type or transformation control strains were followed by significantly higher antifungal activity against V-138I in in vitro assays. The use of Trichoderma spp. for the integrated management of plant diseases caused by V. dahliae requires a better understanding of the molecular mechanisms underlying this interaction that might provide an increase on its efficiency.